2021
DOI: 10.1177/10556656211028506
|View full text |Cite
|
Sign up to set email alerts
|

Final Posttreatment Occlusion in Patients With Unilateral Cleft Lip and Palate

Abstract: Objective: To evaluate final posttreatment occlusion in patients with complete unilateral cleft lip and palate (cUCLP) by comparing (1) 3 treatment centers, (2) males and females, (3) cleft and noncleft sides, (4) right- and left-sided clefts, and (5) orthodontic treatment with/without orthognathic surgery (OS). Design: Retrospective cohort study. Patients: Blinded posttreatment dental casts of 56 patients (19.4 ± 1.4 years) with cUCLP from 3 centers in Switzerland. Main Outcome Measure: Occlusal assessment us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
1
1
Order By: Relevance
“…Right UCLP was noted to have a stronger correlation with dental arch symmetry in a small Brazilian series 49 . Dental arch relationships with sidedness of cleft were inconclusive; in the study by Staudt et al 50 greater maxillary growth for left sided UCLP was reported using Modified Huddart Bodenham scores and overjet whereas Haque et al 51 reported no difference in GOSLON scores between left or right sided UCLP.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Right UCLP was noted to have a stronger correlation with dental arch symmetry in a small Brazilian series 49 . Dental arch relationships with sidedness of cleft were inconclusive; in the study by Staudt et al 50 greater maxillary growth for left sided UCLP was reported using Modified Huddart Bodenham scores and overjet whereas Haque et al 51 reported no difference in GOSLON scores between left or right sided UCLP.…”
Section: Resultsmentioning
confidence: 98%
“…We report a trend in results reported for either worse outcomes in right sided UCL/P or equivalent outcomes by UCL/P sidedness, with the proviso that a quality analysis was not performed. Anatomical and growth studies reporting worse outcomes for right sided UCL/P have reported a greater degree of hypoplasia in multiple tissue types compared to left sided UCL/P 41,47,48,50 . Going forward it may help to advance our knowledge of outcomes in patients with UCL/P if awareness is raised amongst the community that sidedness in UCL/P could have a greater impact than purely in the administrative nomenclature of cleft classification.…”
Section: Discussionmentioning
confidence: 99%
“…осіб із уродженими вадами ЩЛД. Тобто, в середньому, реєструвалося народження одної дитини на 420-450 новонароджених [1][2][3][4].…”
Section: антропометричні особливості обличчя у дітей з уродженими деф...unclassified
“…Previous studies that investigated the association of cleft laterality with school grades in a Norwegian population reported no differences between cleft laterality, whereas two additional studies by the same author that examined the relationship between laterality and academic achievement gave conflicting findings of worse outcomes in left and right clefts 8–10 . When final post‐treatment occlusion in 56 patients with complete UCLP were compared among the right‐ and left‐sided clefts, the outcomes were worse in right‐sided clefts when assessing the labial segment 11 . Regarding facial aesthetics, a retrospective analysis of 76 images of 5‐year‐old patients with a complete UCLP found that surgeon raters scored the aesthetic outcome of right‐sided clefts more severely than those on the left 12 .…”
Section: Introductionmentioning
confidence: 97%
“…[8][9][10] When final post-treatment occlusion in 56 patients with complete UCLP were compared among the right-and left-sided clefts, the outcomes were worse in right-sided clefts when assessing the labial segment. 11 Regarding facial aesthetics, a retrospective analysis of 76 images of 5-year-old patients with a complete UCLP found that surgeon raters scored the aesthetic outcome of right-sided clefts more severely than those on the left. 12 Similarly, a study rating the appearance of 160 children and teenagers reported patients with right UCLP as having poorer appearance than left UCLP.…”
mentioning
confidence: 99%